Las técnicas grafo-plásticas y su incidencia en la creatividad de los niños y niñas de preparatoria, primer grado de educación básica del centro educativo “Víctor Sergio Ron Vega” del cantón Francisco de Orellana, periodo 2013-2014 - Fuelpas Domínguez, María Teresa de Jesús (2014)
This thesis was aimed to investigate as " GRAPH TECHNIC - PLASTIC AND ITS IMPACT ON BASIC EDUCATION FIRST GRADE CHILDREN CREATIVITY “VICTOR SERGIO VEGA RON" FRANCISCO DE ORELLANA CANTON, PERIOD 2013-2014. “. It has been developed in accordance with the Rules of Graduation National University of Loja. In the present investigation the General Objective was to show the importance of using the Graph-techniques and their impact on the Basic Education First Grade Creativity. The methods used in the preparation of this research work were: Scientist, Synthetic, Analytical and Statistical Model, which allowed for the discussion and comparison of the proposed variables. Instruments used were Preparatory Teachers Survey to know if they use Graph - visual techniques in daily work, and an Observation Guide applied to children to determine the level of creativity. Survey applied 100% of teachers often use these types of techniques Graph - plastic : bucking , wrinkled, folded , shaped , torn, snipped , chopped , entronchado and punching; 50% finger paint , armed, interlaced , rainfall , and sgraffito . According to the results of the observation guide concludes that 57% of children have investigated Developing creativity Highly Satisfactory, Satisfactory 37%, and 6% Unsatisfactory